2222. Impact of Sustained Virologic Response Achieved Through Newer Direct Acting Antivirals in Hepatitis C Infection on Diabetes Mellitus. (26th November 2018) - Mada, Pradeep Kumar; Malus, Matthew E; Chen, Bing; Adley, Sharon; Castano, Gabriel; Moore, Maureen; Alam, Mohammed; King, John
Abstract: Background: Hepatitis C virus (HCV) infection is one of the leading causes of mortality and morbidity in the United States with an incidence of about 0.7 cases per 100, 000 population and a prevalence of 2.7 to 3.9 million people. To our knowledge only one study was performed so far to assess the relation between treating hepatitis C virus using direct acting antiviral drugs (DAA) and reduction in the severity of type 2 diabetes mellitus (DM). Our study aims to assess the effect of SVR in hepatitis C virus on type 2 DM. The effect of the management with newer agents leading to sustained virologic response (SVR) on type 2 DM was analyzed in hepatitis C virus infection. Methods: We performed a retrospective chart review in our hepatitis clinic located in Shreveport, Louisiana. Patients with age greater than 18 years old, who has both uncontrolled hepatitis C and type 2 DM, seen in our clinic from November 1, 2014 to December 31, 2017 were included. Hospital electronic health records were screened for diagnosis of hepatitis C and uncontrolled type 2 DM by ICD codes. We performed paired sample t-test between pre- and 6-month post-treatment-values of fasting blood sugar and Body Mass Index (BMI). Results: There was a statistically significant improvement in fasting blood sugar levels following hepatitis C therapy from 184.2 ± 74.8 to 133.06 ± 48.2 ( P < 0.01), with an improvement of 51.2 ± 77.6 respectively ( N = 49).There was a statistically significant improvement in HbA1c levels following hepatitis C therapy from 8.062 ± 1.8 to 7.019 ± 0.96 ( P < 0.05), with an improvement of 1.042 ± 2.03 respectively ( N = 21).There was no statistically significant improvement in BMI levels following hepatitis C therapy from 29.91 ± 6.6 to 29.79 ± 6.7 ( P > 0.05), with slight improvement of 0.11 ± 2.08 respectively ( N = 49). Conclusion: We conclude that there was statistical significant reduction in fasting blood sugar and hemoglobin A1C levels after achieving sustained virological response with new direct antiviral treatment for hepatitis C. A pre- and posttreatment change in body mass index was statistically not significant implies that change in blood sugar level was not due to weight loss. There was no change in diabetic medication during the period of the study or there were no dose adjustments occurred. Disclosures: All authors: No reported disclosures.